2020
DOI: 10.1111/jfpp.15089
|View full text |Cite
|
Sign up to set email alerts
|

Integration of pomegranate peel extract (PPE) with calcium sulphate (CaSO 4 ): A friendly treatment for extending shelf‐life and maintaining postharvest quality of sweet cherry fruit

Abstract: In this work, the effect of pomegranate peel extract (PPE) and calcium sulphate (CaSO4), alone or in combination, on the postharvest quality of sweet cherry fruit was studied at 4°C during 45 days. The results showed that the use of PPE and CaSO4 coatings, alone or in combination, significantly improved the postharvest quality of cherry fruit during storage and decreased weight loss, decay, respiration rate, and increased acidity, firmness, ascorbic acid, DPPH, total phenolic compounds, and total anthocyanin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 83 publications
1
9
0
Order By: Relevance
“…However, the slow rise of SSC in combined coated fruits could be due to the strong hydrogen and covalent interactions between the chitosan network and polyphenolic compounds contained in PPE which could reduce the availability of hydrogen groups required to create hydrophilic bonding with water, resulting in decreased affinity of chitosan film toward water (Siripatrawan & Harte, 2010). Similar results have been observed in apricot fruit coated with chitosan‐enriched PPE extract (Gull et al., 2021); blueberry coated with blueberry leaf extract with chitosan (Yang et al., 2014), and sweet cherry fruit coated with pomegranate peel extract blended with calcium sulfate (Parsa et al., 2020).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, the slow rise of SSC in combined coated fruits could be due to the strong hydrogen and covalent interactions between the chitosan network and polyphenolic compounds contained in PPE which could reduce the availability of hydrogen groups required to create hydrophilic bonding with water, resulting in decreased affinity of chitosan film toward water (Siripatrawan & Harte, 2010). Similar results have been observed in apricot fruit coated with chitosan‐enriched PPE extract (Gull et al., 2021); blueberry coated with blueberry leaf extract with chitosan (Yang et al., 2014), and sweet cherry fruit coated with pomegranate peel extract blended with calcium sulfate (Parsa et al., 2020).…”
Section: Discussionsupporting
confidence: 71%
“…Chitosan coating possesses good mechanical properties (Flores et al., 2016) and prevents loss of moisture from fruit surface thus delay the fruit softening (Xin et al., 2017). While the blended PPE may reduce the activities of cell wall degrading enzymes responsible for the fruit softening (Parsa et al., 2020). The polysaccharide‐based CH coating had the ability to suppress the cell wall structure loosening enzymes thereby delay the ripening and respiration process during storage (Gull et al., 2021; Kumar et al, 2020,2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, since LM consist mostly of volatile terpenoids and non-terpenoid constituents and not lipids, the contribution of LM to weight loss reduction may be minimal [ 86 , 87 ]. However, some authors have outlined that both LM and PP, when added to coatings, may contribute to weight loss reduction because of their lipophilic nature, which possibly reduces gas diffusion and losses in weight due to the respiratory process [ 44 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Azarakhsh et al [ 44 ] also demonstrated that the addition of LM (0.1–0.3%) to sodium alginate coatings significantly reduced R CO2 of fresh-cut apples because of the lipophilic nature of LM, which possibly reduced gas diffusion. Likewise, some authors have reported that PP exhibits lipophilic properties, which improve barrier properties of coatings and thereby minimizing gas diffusion [ 88 ].…”
Section: Discussionmentioning
confidence: 99%